Lessons for climate policy from behavioral biases towards COVID-19 and climate change risks. (January 2021) - Botzen, Wouter; Duijndam, Sem; van Beukering, Pieter
Highlights: The COVID-19 pandemic can be viewed as a rapid learning experiment about how to cope more effectively with climate change. Using insights into behavioral biases, we illustrate parallels between decisions about COVID-19 and climate change risks. Climate change can be mitigated by policies that work with, instead of against, an individual's risk perceptions and biases. We conclude with recommendations for communication policies that make people pay attention to climate change risks. Government responses to the COVID-19 crisis should be linked with environmental sustainability and climate action. Abstract: COVID-19 and climate change share several striking similarities in terms of causes and consequences. For instance, COVID-19 and climate change affect deprived and vulnerable communities the most, which implies that effectively designed policies that mitigate these risks may also reduce the widening inequalities that they cause. Both problems can be characterized as low-probability–high consequence (LP-HC) risks, which are associated with various behavioral biases that imply that individual behavior deviates from rational risk assessments by experts and optimal preparedness strategies. One could view the COVID-19 pandemic as a rapid learning experiment about how to cope more effectively with climate change and develop actions for reducing its impacts before it is too late. However, the ensuing question relates to whether the COVID-19 crisis and its aftermath will speed up climate change mitigation and adaptation policies, which depends on how individuals perceive and take action to reduce LP-HC risks. Using insights into behavioral biases in individual decisions about LP-HC risks based on decades of empirical research in psychology and behavioral economics, we illustrate how parallels can be drawn between decision-making processes about COVID-19 and climate change. In particular, we discuss six important risk-related behavioral biases in the context of individual decision making about these two global challenges to derive lessons for climate policy. We contend that the impacts from climate change can be mitigated if we proactively draw lessons from the pandemic, and implement policies that work with, instead of against, an individual's risk perceptions and biases. We conclude with recommendations for communication policies that make people pay attention to climate change risks and for linking government responses to the COVID-19 crisis and its aftermath with environmental sustainability and climate action.